(untitled) (Педагогіка вищої та середньої школи, 2007)
Article is devoted to a problem of development of ear for music, a substantiation of methods and principles of activization of acoustical representations on employment (occupations) of solfeggio for students of musical-pedagogical faculties of higher educational institutions.